Properties of the stabilizate and possibilities of its utilization - Bajer, Tomáš; Rusek, Vlastimil; Černohorský, Tomáš; Brunclík, Tomáš; Bečková, Veronika; Sákra, Tomáš (Univerzita Pardubice, 2000)
The paper is devoted to production of the stabilizate as a procedure for utilization of wates from coal burning and desulfurization process in heat power stations. This study completes the knowledge concerning the leachability of several metals (As, Al, Cr, V) and some properties of the stabilizate - pH and changes of conductance - in dependence on the method of stabilizate production and on the age of samples. The composition of the stabilizate presenting the best properties has been suggested. Future studies should focus on verification of these results during the longer time period.
Keywords: ochrana životního prostředí; spalování; uhlí; teplárny; recyklace odpadů; desulfurizace